Stranger planet - Pyle, Nathan W (Morrow Gift, 2020)
Features a second volume of "Strange Planet" webcomic strips featuring aliens interacting in a human world. Humorously depicts the aliens encountering music, traditions, pets, fear, pain, and sports.